Nasopharyngeal teratoma - Güney, Ercihan; İmamoğlu, Mehmet and Kandemir, Bedri (The Turkish Journal of Pediatrics, 1986)
The case of an infant with nasopharyngeal teratoma in association with congenital horn-like skin lesions and causing respiratory distress and difficulty in feeding, is reported.